Effect of prophylactic abdominal drainage on postoperative pain in laparoscopic hemicolectomy for colon cancer: a single-center observational study in Korea - Sung Seo Hwang; Heung-Kwon Oh; Hye-Rim Shin; Tae-Gyun Lee; Mi Jeong Choi; Min Hyeong Jo; Hong-min Ahn; Hyeonjeong Park; Hyun Hee Sim; Eunjeong Ji; Anuj Naresh Singhi; Duck-Woo Kim; et al. (Journal of Minimally Invasive Surgery)
Purpose: This study aimed to evaluate the effect of prophylactic abdominal drainage (AD) in laparoscopic hemicolectomy, focusing on assessing postoperative pain outcomes. Methods : Patients were categorized into two groups: those with and without AD (AD group vs. no-AD group). A numerical rating scale (NRS) was used to assess postoperative pain on each postoperative day (POD). Further, the inverse probability of treatment weighting (IPTW) method was used to reduce intergroup bias. Results : In total, 204 patients who underwent laparoscopic hemicolectomies by a single surgeon between June 2013 and September 2022 at a single institution were retrospectively reviewed. After adjusting for IPTW, NRS scores on POD 2 were significantly lower in the no-AD group (3.2 ± 0.8 vs. 3.4 ± 0.8, p = 0.043). Further examination of postoperative outcomes showed no statistically significant differences in complications between the AD (17.3%) and no-AD (12.4%) groups (p = 0.170). The postoperative length of hospital stay was 7.3 ± 2.8 days in the AD group and 6.9 ± 3.0 days in the no-AD group, with no significant difference (p = 0.298). Time to first flatus was 3.0 ± 0.9 days in the AD group and 2.7 ± 0.9 days in the no-AD group, with no significant difference (p = 0.078). Regarding readmission within 1 month, there were four cases each in the AD (2.3%) and no-AD (1.7%) groups, with no significant difference (p = 0.733). Conclusion : Laparoscopic hemicolectomy without AD resulted in no significant differences in postoperative clinical outcomes, except for postoperative pain. This finding suggests that prophylactic AD may exacerbate postoperative pain.